The Implementation Of Polygamy Law: Indonesian Women Marrying Malaysian Men in Satun, Thailand - Umi Kalsum; Akbarizan Akbarizan (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
One fundamental human need, which requires a highly specific solution, is the fulfillment of sexual desires, with marriage serving as its gateway. Therefore, a man who is already married may go to great lengths to marry again. Cross-border polygamous marriages involving Indonesian women and Malaysian men, conducted in Satun, Thailand, present a complex legal phenomenon. This study aims to analyze the implementation of laws governing such marriages under Indonesian, Malaysian, and Thai legal systems, as well as their impact on the legal status of the marriage, women's rights, and legal recognition in each country. The findings reveal that cross-border marriages often fail to fulfill registration procedures in the home country, rendering them legally unrecognized in Indonesia and Malaysia. In Thailand, Islamic law applied in Satun permits polygamy, but such recognition is local and does not automatically extend across national borders. This study recommends strengthening legal cooperation among countries to provide better legal protection for couples and related parties involved in cross-border marriages.